Two dimensional modelling for catalytic combustion - Nor Faezah, Hamzah (2007)
Potential of catalytic combustion as a method of NOx emission in gas turbine application have been realized, but research in this area never been higher. Catalysts properties assist chemical reactions by affecting the rate of reaction. It allows fuel oxidation at temperature below flammability limit. In this research, simulation using CFD commercial code in catalytic combustion needed and using a simple steady state laminar flow, thus, a 2D catalytic combustion was modeled and simulated. Using Fluent software and the mathematical models available for species transport and wall surface reaction, the results provided by Dogwiler of The Paul Scherrer Institute in Switzerland, been compared qualitatively. The effect of some design parameters, such as the gas mixture inlet velocities and equivalence ratio On the heterogeneous reaction were validate.